2142. Safety and immunogenicity of COVID Influenza Combination Vaccine. (15th December 2022) - Shinde, Vivek; Woo, Wayne; Liu, Sharon; Cook, Sara; Santiago, Zenaida; Neal, Susan; Plested, Joyce S; Vincent, Tim; Zhu, Mingzhu; Cloney-Clark, Shane; Cho, Iksung; Fries, Lou; et al.
Abstract: Background: We developed a COVID-Influenza Combination (CIC) vaccine, comprising recombinant SARS-CoV-2 Spike (rS) and quadrivalent influenza hemagglutinin (HA) protein nanoparticles (qNIV), and Matrix-M TM adjuvant. rS/Matrix-M previously demonstrated efficacy against COVID-19 in Phase 3 trials, while qNIV/Matrix-M previously demonstrated induction of broadly cross-reactive antibodies. Here we report preliminary safety and immunogenicity results of a first-ever Phase 1/2 CIC dose-finding trial. Methods: Seropositive (COVID-19 vaccinated ≥ 8 weeks prior) participants (N=642) aged 50-70 years were randomized equally, to receive two intramuscular doses, 56 days apart, to 1 of 14 different dose/formulations of CIC using a design of experiments approach (dose range: rS 2.5-22.5ug, HA 5-60ug; and 50ug Matrix-M), or to 1 of 2 reference formulations of either standalone rS with Matrix-M [2 doses] or qNIV with Matrix-M [1 dose only]. Pre- and post-vaccination (Days 0, 28, 56, 70, 84, 182) immunogenicity assessments including SARS-CoV-2 anti-S IgG and influenza HAI antibodies to vaccine-homologous strains. Reactogenicity was assessed 7 days following each dose, and safety outcomes assessed through Day 70. Multiple regression was used to create predictive models to assess antibody response surfaces and for dose optimization. Results: All CIC formulations were well tolerated, with a reactogenicity and safety profile generally comparable to standalone rS or qNIV. Regression modelling of post-first dose responses revealed that both rS and HA antigens in a CIC formulation modestly interfered with each other, however, interference was overcome with dose adjustment across a range of rS/HA doses. Specifically, higher rS dose ( >20ug), in a dose dependent fashion, overcame HA interference, closely matching standalone rS IgG reference responses (GMEU 16, 818), whereas lower, intermediate HA dose overcame rS interference, closely matching standalone HA reference HAI responses for H3N2 (GMT 145), H1N1 (GMT 134), and B-Victoria (GMT 66); while modestly (at least 34%) lower than the reference B-Yamagata response (GMT 101). Conclusion: CIC formulations were well tolerated and immunogenic, with various dose combinations achieving response comparable to standalone vaccines. Disclosures: Vivek Shinde, MD, MPH, Novavax Inc.: Stocks/Bonds Wayne Woo, MS, Novavax Inc.: Stocks/Bonds Sharon Liu, n/a, Novavax Inc.: Stocks/Bonds Sara Cook, n/a, Novavax Inc.: Stocks/Bonds Zenaida Santiago, n/a, Novavax Inc.: Stocks/Bonds Susan Neal, n/a, Novavax Inc.: Stocks/Bonds Joyce S. Plested, n/a, Novavax Inc.: Stocks/Bonds Tim Vincent, n/a, Novavax Inc.: Stocks/Bonds Mingzhu Zhu, n/a, Novavax Inc.: Stocks/Bonds Shane Cloney-Clark, n/a, Novavax Inc.: Stocks/Bonds Iksung Cho, MS, Novavax Inc.: Stocks/Bonds Lou Fries, n/a, Novavax Inc.: Stocks/Bonds Greg Glenn, n/a, Novavax Inc.: Stocks/Bonds.